TM7 (Saccharibacteria) regulates the synthesis of linolelaidic acid and tricosanoic acid, and alters the key metabolites in diapause Clanis bilineata tsingtauica - Qian, Lei; Chen, Bo-jian; Deng, Pan; Gui, Fu-rong; Cao, Ye; Qin, Yi; Liao, Huai-jian (Frontiers in Physiology, 2023)
Good exploitation and utilization of edible insects can effectively alleviate global food security crisis in years. The study on diapause larvae of Clanis bilineata tsingtauica (DLC) was conducted to explore how gut microbiota regulate the nutrients synthesis and metabolism of edible insects. The results showed that C. bilineata tsingtauica maintained a total and stable nutrition levels at early phase of diapause. The activity of instetinal enzymes in DLC fluctuated markedly with diapause time. Additionally, Proteobacteria and Firmicutes were the predominant taxa, and TM7 (Saccharibacteria) was the marker species of gut microbiota in DLC. Combined the gene function prediction analysis with Pearson correlation analysis, TM7 in DLC was mainly involved in the biosynthesis of diapause-induced differential fatty acids, i.e., linolelaidic acid (LA) and tricosanoic acid (TA), which was probably regulated by changing the activity of protease and trehalase, respectively. Moreover, according to the nontarget metabolomics, TM7 might regulate the significant differential metabolites, i.e. D-glutamine, N-acetyl-d-glucosamine and trehalose, via the metabolism of amino acid and carbohydrate pathways. These results suggest that TM7 increased LA and decreased TA via the intestinal enzymes, and altered intestinal metabolites via the metabolism pathways, maybe a key mechanism for regulating the nutrients synthesis and metabolisms in DLC.